P1.54 Development and evaluation of in- house multiplex real-time pcr for detection of neisseria gonorrhoeae, chlamydia trachomatis and mycoplasma genitalium infection in infertility patients. (8th July 2017) - Sethi, Sunil; Roy, Amit; Yadev, Rakesh; Dadwal, Rajneesh; Chakraborti, Anuradha; Dhaliwal, Lakhbir
Abstract : Introduction: C.trachomatis, N.gonorrhoeae and M.genitalium are important cause of infertility but detection is usually by PCR which has to be performed indvidually for each pathogen.The aim of this study was to develop In house multiplex Real time PCR assay for simultaneous detection of all these pathogens in single run and will also help in detecting co infecion if present thus saving cost and time in cases of infertility. Methods: The Taqman probe based multiplex qPCR for detection of C.trachomatis, N.gonorrhoeae and M.genitalium was developed using different primers and probes. Analytical sensitivity of multiplex qPCR was determined using pGEMT Easy vector cloned with target genes. The detection limit for each organism was determined using 10 fold dilutions of targets. The multiplex qPCR was evaluated in 248 clinical samples i.e 98 infertile (endometrial biopsy and endocervical swabs) and 150 healthy controls (endocervical swabs). The sensitivity, specificity, positive and negative predictive value (PPV and NPV) of multiplex qPCR was calculated. Results: The sensitivity, specificity, PPV and NPV of new multiplex qPCR was 98.80%, 100%, 100% and 99.69% respectively compared to uniplex qPCR. The discordant result of multiplex qPCR was detected in 1 sample. Developed multiplex qPCR showed 100% sensitivity, specificity, PPV and NPV for C.trachomatis and N.gonorrhoeae respectively. The sensitivity, specificity, PPV and NPV for M.genitalium were 97.78%, 100%, 100% and 99.72% respectively. No cross-reactions were detected between target organisms or with related species. Conclusions: Multiplex In house qPCR in this study has shown high sensitivity and specificity for detection of C.trachomatis, N.gonorrhoeae and M.genitalium in infertility patients which facilitate the opportunity to be used as a rapid diagnostic tool and for initiation of early treatment in resource poor settings where syndromic approach is being followed. This assay needs to be performed on the larger sample size and using different specimens prior to large-scale screening.